2018
DOI: 10.29359/bjhpa.10.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies, perception of sport risk and satisfaction with life in men and women practicing extreme sports

Abstract: Background: Few studies concern strategies for coping with stress in people who practice extreme sports. The goal of the current work is to analyse the relationships between strategies for coping with stress used by male and female extreme athletes, perception of threat associated with their sport, and their satisfaction with life. Material and methods:The sample consisted of 144 athletes, 55 females and 89 males, who have practiced extreme sports for at least 2 years. Participants completed the Brief COPE que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…When others influenced the stress and coping process situations were more likely to be appraised as a challenge and more adaptive problem- and emotion-focused strategie s were used, whereas when a stressor was appraised as a threat a more maladaptive coping strategy or no coping at all was reported ( 23 , 45 ). The results also revealed that there is a significant relationship between coping with stress and perceptions of risk in extreme athletes, practicing extreme sports ( 43 ).…”
Section: Resultsmentioning
confidence: 91%
“…When others influenced the stress and coping process situations were more likely to be appraised as a challenge and more adaptive problem- and emotion-focused strategie s were used, whereas when a stressor was appraised as a threat a more maladaptive coping strategy or no coping at all was reported ( 23 , 45 ). The results also revealed that there is a significant relationship between coping with stress and perceptions of risk in extreme athletes, practicing extreme sports ( 43 ).…”
Section: Resultsmentioning
confidence: 91%
“…For the participants of this study, the most important goals were associated with physical fitness, having a fit body, and health, and thus they were no different from those most commonly indicated by individuals who engage in forms of physical activity and sport that are not associated with increased risk [ 31 ]. This may be caused by the fact that individuals who engage in HRS and ES do not assess their sport disciplines as extremely dangerous [ 38 ], and thus their attitude is not significantly different from that of people who practice non-risky disciplines. One can speculate that providing oneself with desired levels of stimulation from risky forms of physical activity may thus be a latent and indirect motive, one that is not expressed in declarative statements about goals typical of any physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially at the beginning, research has focused on arguing for the negative effects depending on several variables, (gender, age, sports, etc) at physical level: high risk-taking levels produce lesions and even death [16,24,26,37], sleep disturbances [28], but also pathological personality disorders (narcissism, anxiety, neuroticism, addictions), corelated with compulsive and deviant behaviours (pathological abuse and addiction to drugs, alcohol, sport) [2], [14,15], [29], [38]. Recent studies have focused on the benefits on physical performance, mental health, and personality traits, on emotion management -courage, humility, fear [7,8], [10], [27], [40], [46], physical, emotional, and mental freedom [9], psychological recovery and emotional well-being [3], [25] even among people suffering from hyperkinetic disorders (ADHD) [42], self-control and stress management, self-knowledge and self-achievement [12], [21], [23], [31,32].…”
Section: The Consequences Of Extreme Sports Developmentmentioning
confidence: 99%
“…and political impact refers to: increased interest for organising extreme sports events, introduction of prizes and development of local-host communities for these events -local infrastructure, sports facilities [6], [31] involving an increase in sports tourism, in both practitioners and spectators [19], [22,23], [39]; an increase in the interest for advertising from the part of certain international -but also local and national -brands, thus determining increased consumerism and corporate interest through the emergence of a huge industry [11], [18], [30]; corelation of sports tourism with other activities such asecologic, rural, medical etc, tourism; (re)vitalisation of places / communities; investments in equipment [44]. All these events may be possible if legislative changes areproduced at both national and international level: -adopting laws and regulations to facilitate the management and control of sports events [22], [45], the territorial mobility and the medical insurance for athletes and spectators.…”
Section: Postmodernismmentioning
confidence: 99%